Intestinal ischemic preconditioning ameliorates hepatic ischemia/reperfusion injury in rats: Role of heme oxygenase 1 in the second window of protection. Issue 1 (January 2015) - Kageyama, Shoichi; Hata, Koichiro; Tanaka, Hirokazu; Hirao, Hirofumi; Kubota, Toyonari; Okamura, Yusuke; Iwaisako, Keiko; Takada, Yasutsugu; Uemoto, Shinji
<x xml:space="preserve">Abstract</x> Preconditioning by brief ischemia protects not only the concerned organ but also other distant organs against subsequent lethal damage; this is called remote ischemic preconditioning (RIPC). This study was designed to investigate the impact of intestinal RIPC on hepatic ischemia/reperfusion injury (IRI) with a special interest in heme oxygenase 1 (HO‐1) induction in the second window of protection (SWOP). Male Wistar rats were randomly assigned to 1 of 2 groups: an RIPC group or a sham group. Before hepatic IRI, either intestinal RIPC, consisting of 2 cycles of 4‐minute superior mesenteric artery clamping separated by 11 minutes of declamping (RIPC group), or a sham procedure (sham group) was performed. After 48 hours of recovery, the rats were exposed to 30 minutes of total hepatic IRI. Transaminase releases and proinflammatory cytokines were determined at several time points after reperfusion. Histopathological analysis and animal survival were also investigated. Intestinal RIPC significantly lowered transaminase release (alanine aminotransferase at 2 hours: 873.3 ± 176.4 IU/L for the RIPC group versus 3378.7 ± 871.1 IU/L for the sham group, P < .001) as well as proinflammatory cytokine production (tumor necrosis factor α at 2 hours: 930 ± 42 versus 387 ± 17 pg/μL, P < .001). The morphological integrity of the liver and the ileum was maintained significantly better with intestinal RIPC; this reached statistical significance not only in Suzuki's liver injury score (3.5 ± 0.2 versus 0.7 ± 0.5, P = .007) but also in Park's score for intestinal damage (4.0 ± 0.4 versus 2.0 ± 0.2, P = .007). Animal survival was also markedly improved (83.1% versus 15.4%, P < .001). As a mechanism underlying this protection, HO‐1 was substantially induced in liver tissue, especially in hepatocytes, with remarkable up‐regulation of bradykinin in the portal blood, whereas HO‐1 protein induction in enterocytes was not significant. In conclusion, intestinal RIPC remarkably attenuates hepatic IRI in the SWOP, presumably by HO‐1 induction in hepatocytes. Liver Transpl 21:112‐122, 2015. © 2014 AASLD.